Analisis Strategi Pemasaran Produk Hidroponik (Studi Kasus Pada UMKM Aa818_Hydroponic) - Yoga Aji Pradana; Kusnandar Kusnandar (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2023)
The vegetables cultivated by Aa818_Hydroponic are pesticide-free hydroponic vegetables. Aa818_Hydroponic markets 13 types of vegetables using the same method and strategy. The research aims to find out internal and external factors that are strengths, weaknesses, opportunities, and threats for marketing, to find out alternatives and appropriate strategic priorities in marketing hydroponic vegetable products to Aa818_Hydroponic MSMEs. The research uses descriptive analytical methods with implementation techniques through observation and in-depth interviews. Key informants consisted of experts, practitioners, and consumers using questionnaires. The analysis method uses the SWOT and ANP matrices. The research results show that Aa818_Hydroponic has strengths, namely competitive vegetable prices, having a variety of vegetable products, free shipping promotions, long-lasting freshness levels, and vegetable products free from pesticides. Weaknesses include not having strong branding, packaging that is not attractive enough, the location of the plantation is not strategic, online promotion is not optimal, and human resources are limited. Opportunities include support from the government, many expo activities, fairs and exhibitions, good consumer perception of hydroponic vegetables, changes in healthy lifestyles, creation of opportunities for technological developments for marketing. The threats they have are that substitute product prices are cheaper, competitors' packaging is more attractive, competitors' marketing is more effective, and pest and disease attacks. SWOT analysis produces seven marketing strategies. ANP analysis produces the main strategic priority, namely participating in exhibition activities to promote existing advantages.